(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The term “integral planning” describes the creative cooperation of experts from different disciplines with the aim of solving a complex, technical planning task. By involving all the disciplines and stakeholders at an early stage it is possible to achieve better solutions than in a linear planning process in which one designer directs the specifications to the respective specialist planners, who then add the corresponding engineering services. In the course “Integral Planning”, students from the fields “Architecture – Green Building” and “Civil Engineering – Construction Management” are working on a project in an interdisciplinary exchange over two semesters. Through the simultaneous interweaving of their specific skills, combined with a very free working method, the students are taught integral planning in a realistic setting with the aim to design a modular timber building system for temporary educational buildings according to the “cradle to cradle” principle.